Springer handbook of mechanical engineering - Grote, Karl-Heinrich; Antonsson, Erik K. (Springer, 2009)
"Covers numerous relevant mechanical engineering topics. Functions as a guide for people who design, develop, manufacture, operate, and use mechanical artifacts."--Publisher description.